2009
DOI: 10.1111/j.1750-3841.2009.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Evaluation of Transgenic, Thaumatin II‐Producing Cucumber Fruits

Abstract: Fruits of transgenic cucumber lines expressing preprothaumatin II gene were evaluated concerning their aroma. Four homozygous lines, that is, 210 06, 212 01, 224 09, and 225 03 with different levels of transgene expression were selected. Recipient line cv. Borszczagowski, which was formed by inbred line of Cucumis sativus L., was used as a control. The experiment was carried out in a greenhouse and an outdoor experimental plot. The aroma of cucumber fruits was evaluated by GC/MS, as well as GC/MS/TOF in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Fruit and vegetables can produce aroma volatile compounds to form characteristic flavor, which are associated with quality changes during storage (Zawirska‐Wojtasiak, Gośliński, Szwacka, Gajc‐Wolska, & Mildner‐Szkudlarz, ). GC–MS is a typical method for volatile organic compounds, and has been applied well in various food analyses (Lee, Jeong, & Ku, ; Sun, Zhang, Chen, Zheng, & Fang, ).…”
Section: Resultsmentioning
confidence: 99%
“…Fruit and vegetables can produce aroma volatile compounds to form characteristic flavor, which are associated with quality changes during storage (Zawirska‐Wojtasiak, Gośliński, Szwacka, Gajc‐Wolska, & Mildner‐Szkudlarz, ). GC–MS is a typical method for volatile organic compounds, and has been applied well in various food analyses (Lee, Jeong, & Ku, ; Sun, Zhang, Chen, Zheng, & Fang, ).…”
Section: Resultsmentioning
confidence: 99%
“…In another study on the profiles of aroma compounds of four lines of GM cucumber using GC-MS, solid-phase microextraction provided better results in terms of number of extracted volatile compounds than microdistillation [90]. The analysis of cucumber extracts using GC-EI-Q-MS and GC-EI-TOF-MS suggested that the significant differences found between GM and non-GM varieties were quantitative rather than qualitative, regardless of the MS-based technique used.…”
Section: Gc-msmentioning
confidence: 90%
“…In cucumber (Cucumis sativus), the concentration of the volatile that mainly contributes to its aroma, (E, Z)-2,6 nonadienal (Table 1), was increased by overexpressing preprothaumatin II (thaumatin II is initially translated as preprothaumatin with peptides in C terminus that are cleaved off when the protein matures). Transgenic fruits presented a higher sensory perception of fruit flavor and increased levels of this aldehyde and other volatiles [66].…”
Section: Metabolic Engineering Of Fruit Volatiles Derived From Fatty mentioning
confidence: 99%